INOVASI PEMBELAJARAN PAI DI MASA PANDEMI COVID-19 DAN IMPLIKASINYA PADA AL-AKHLAQ AL-KARIMAH - J. Nabiel Aha Putra; Nur Abdul Kholik Nugroho (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2020)
The covid-19 pandemic has had a big enough impact on countries in the world, especially what we feel in Indonesia. The government has recommended implementing the three measures, namely wearing masks, washing hands and maintaining distance. Educators in this case think hard to find innovation, to maintain the morals of students. This research method uses a literature review, with a descriptive qualitative approach. This study aims to analyze learning innovations, opportunities and challenges, supporting and inhibiting factors and their implications for al-Akhlaq al-Karimah. The results of the analysis show that during the pandemic, all learning innovation through information technology is very much needed, taking into account the opportunities and challenges for educators and students, as well as the existence of supporting and inhibiting factors for educators and students. They will be able to adapt well, so that it will produce positive and negative impacts for students and educators and will also have an impact on al-Akhlaq al-Karimah.